Research in the field of psychopedagogy - Mamede-Neves, M. Apparecida; Pain , Sara (Seven Editora, 2023)
The article discusses the specificity of the type of research appropriate to the field of Psychopedagogy, through the interlocution between the two authors who sign the chapter. Being both structuralists, they are based on this philosophical school when discussing reasons to recognize qualitative research as being the most appropriate when it comes to clinical Psychopedagogy, both because of the conditions of the work setting – a praxis – as well as about the client. DOI:https://doi.org/10.56238/ptoketheeducati-020